Family Policy in the Context of the Transition to Sustainable Development: A Comparative Analysis of Russia and Kazakhstan - Iskakova, Zhuldyzay; Kalashnikova, Nataliya (International Journal of Criminology and Sociology, 2022)
Despite the crisis of values that is characteristic of many countries in the world, family remains the focus of the state policy for most of them. It is recognized as the basic social unit of society, whose level of development inevitably affects the progress of the entire society. In this sense, families are active agents for achieving sustainable development goals. Thus, the progress of families will inevitably affect the progress of their communities and societies. This research paper considers a wide range of issues relating to family policy in Central Asian countries, with particular emphasis on the national policy in the field of family relations in Kazakhstan and Russia. The authors consider the concept of family policy and its impact on the family institution, study the role and importance of such a policy in the modern context, as well as analyze the conditions for the formation of the family policy during the USSR period and after the independence of the Russian Federation and the Republic of Kazakhstan.